An Update on Heart Transplantation in Human Immunodeficiency Virus–Infected Patients. Issue 1 (2nd November 2015) - Agüero, F.; Castel, M. A.; Cocchi, S.; Moreno, A.; Mestres, C. A.; Cervera, C.; Pérez‐Villa, F.; Tuset, M.; Cartañà, R.; Manzardo, C.; Guaraldi, G.; Gatell, J. M.; et al.
Abstract: Cardiovascular diseases have become a significant cause of morbidity in patients with human immunodeficiency virus (HIV) infection. Heart transplantation (HT) is a well‐established treatment of end‐stage heart failure (ESHF) and is performed in selected HIV‐infected patients in developed countries. Few data are available on the prognosis of HIV‐infected patients undergoing HT in the era of combined antiretroviral therapy (cART) because current evidence is limited to small retrospective cohorts, case series, and case reports. Many HT centers consider HIV infection to be a contraindication for HT; however, in the era of cART, HT recipients with HIV infection seem to achieve satisfactory outcomes without developing HIV‐related events. Consequently, selected HIV‐infected patients with ESHF who are taking effective cART should be considered candidates for HT. The present review provides epidemiological data on ESHF in HIV‐infected patients from all published experience on HT in HIV‐infected patients since the beginning of the epidemic. The practical management of these patients is discussed, with emphasis on the challenging issues that must be addressed in the pretransplant (including HIV criteria) and posttransplant periods. Finally, proposals are made for future management and research priorities. Abstract : The authors fi nd that the survival rate of HIV‐infected patients undergoing heart transplantation in the highly active antiretroviral therapy (HAART) era is much better than in the pre‐HAART era, and they discuss the challenging issues that must be addressed in the pretransplant and posttransplant periods.